2023
DOI: 10.1001/jamanetworkopen.2022.54573
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prescribed Opioid Dosages Among Patients Receiving Medical Cannabis for Chronic Pain, New York State, 2017-2019

Abstract: ImportancePatients with chronic pain often receive long-term opioid therapy (LOT), which places them at risk of opioid use disorder and overdose. This presents the need for alternative or companion treatments; however, few studies on the association of medical cannabis (MC) with reducing opioid dosages exist.ObjectiveTo assess changes in opioid dosages among patients receiving MC for longer duration compared with shorter duration.Design, Setting, and ParticipantsThis cohort study of New York State Prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…Reduction of opioid use concomitant with cannabis use (Kim et al, 2016; Nguyen et al, 2023; Pardo, 2017; Piper et al, 2017; Shi, 2017) may arise because cannabis acts therapeutically to reduce the motivation to seek opioids, because it is substituting for the opioid or because it is enhancing the impact of a unit dose of the opioid. Cannabis smoking slightly increased the abuse-related subjective effects of oxycodone in a human laboratory study (Cooper et al, 2018), but self-administration was not directly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of opioid use concomitant with cannabis use (Kim et al, 2016; Nguyen et al, 2023; Pardo, 2017; Piper et al, 2017; Shi, 2017) may arise because cannabis acts therapeutically to reduce the motivation to seek opioids, because it is substituting for the opioid or because it is enhancing the impact of a unit dose of the opioid. Cannabis smoking slightly increased the abuse-related subjective effects of oxycodone in a human laboratory study (Cooper et al, 2018), but self-administration was not directly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with prior research that found medical cannabis laws were associated with lower prescription opioid prescribing. [35][36][37][38]64 Importantly, prior research indicates that the effect of medical cannabis laws likely took several years to manifest. 34 This is a logical finding as behavior change associated with public policy typically requires time, especially when removing a restrictive policies, such as legalizing the medical sale of cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large focus on opioids, this suggests that producers (and consumers) of CBD expect the products to be used as an alternative to opioids (Capano et al, 2020). These claims may partially be based on the literature related to the substitution patterns between cannabis and other psychoactive agents, largely related to the legalization of recreational or medicinal marijuana (Nguyen et al, 2023). Many of these studies provide estimates suggesting that alcohol and marijuana serve as substitutes (Chaloupka & Laixuthai, 1997; Crost & Guerrero, 2012; Crost & Rees, 2013; DiNardo & Lemiuex, 2001; Wen et al, 2015), while others find that alcohol and marijuana may actually have a complementary relationship (Pacula, 1998; Saffer & Chaloupka, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Looking at opioids specifically, Nielsen et al (2022) finds that preclinical and observational studies often find opioid-sparing effects of cannabinoids, but these effects are inconsistent in RCT's. Interestingly, a study by Capano et al (2020) finds that over half of chronic pain patients reduced or eliminated opioids 8 weeks after adding CBD-rich hemp extract to their diet, where Nguyen et al (2023) have found that medical cannabis does reduce opioid use for chronic pain. Therefore, CBD use appears to have the potential for clinical therapeutic potential for chronic pain, though more evidence is needed; individuals, on the other hand, view CBD as an effective treatment for pain.…”
Section: Introductionmentioning
confidence: 99%